Development of parkinsonism after long-standing cervical dystonia: a cohort - Balint, Bettina; Mulroy, Eoin; Gövert, Felix; Latorre, Anna; Di Lazarro, Giulia; Erro, Roberto; Batla, Amit; Holton, Janice L.; Miki, Yasuo; Warner, Thomas T.; Bhatia, Kailash P. (Journal of the neurological sciences, 2021)
Introduction - Dystonia occurring in the context of parkinsonism is well-known, e.g. as foot dystonia in young-onset Parkinson's disease (PD), anterocollis in multisystem atrophy (MSA) or blepharospasm (levator inhibition) in progressive supranuclear palsy. We have, however, encountered a series of patients whose phenotype differed from the above described entities. - Methods - We describe a cohort of patients in whom typical idiopathic isolated (primary) late-onset focal or segmental (predominantly cervical) dystonia preceded the development of parkinsonism by several years, sometimes decades. - Results - In a cohort of 450 patients followed in our botulinum toxin injections clinic, we identified 11 (2.4%; 7 women) who developed parkinsonism at a median of 14 years after the onset of dystonia. Median age at onset of parkinsonism was 70 years (range 59-87), usually manifesting with a new tremor or a change of tremor pattern, complaints of ‘slowing down’ or new walking difficulties. Parkinsonism resembled PD in 5 (one pathologically confirmed); the remainder had atypical parkinsonism of MSA (n = 3) or indeterminate phenotype (n = 3). - Conclusion - The relatively frequent occurrence of parkinsonism after long-standing dystonia would suggest a link between the two, in line with evidence from other clinical reports, imaging studies, animal models and genetics. It appears that in some cases of dystonia this could be an antecedent manifestation of a syndrome with parkinsonism developing later, or be a risk factor for parkinsonism. In practice, it is important for clinicians to be alert to new symptoms/signs in patients with long-standing dystonia. From a research point of view, longitudinal case-control studies would be required to further investigate the link between long-standing dystonia and subsequent parkinsonism.